Automatically assembled large-scale tensegrities by truncated regular polyhedral and prismatic elementary cells. (15th January 2018) - Zhang, Li-Yuan; Li, Song-Xue; Zhu, Shi-Xin; Zhang, Bo-Yang; Xu, Guang-Kui
Abstract: As a novel type of reticulated structures, tensegrities have found various applications in science and engineering. In this paper, an ingenious assembly method is developed to construct large-scale tensegrities using truncated regular polyhedral tensegrities and prismatic tensegrities as elementary cells. The truncated polyhedral tensegrities with regular polygons on their surfaces are specified as islands, and the prismatic tensegrities are used as bridges to connect these polygons along different directions. This method allows us to construct many types of large-scale tensegrities satisfying the demands of the size and topology. Based on the node-on-node assembly scheme, Z-based truncated regular octahedral tensegrity and its matching quadruplex prismatic tensegrity are employed to produce representative examples with traditional and untraditional shapes. Their mechanical properties are evaluated from the viewpoints of self-equilibrium, stability, and mechanical responses. Our results help to manufacture demanded large-scale tensegrities with delicate mechanical properties, and may be beneficial to construct composite metamaterials.